2018
DOI: 10.3390/rs10020310
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Interpolation of Cloudy SST Fields Using Conditional Analog Data Assimilation

Abstract: The ever increasing geophysical data streams pouring from earth observation satellite missions and numerical simulations along with the development of dedicated big data infrastructure advocate for truly exploiting the potential of these datasets, through novel data-driven strategies, to deliver enhanced satellite-derived gapfilled geophysical products from partial satellite observations. We here demonstrate the relevance of the analog data assimilation (AnDA) for an application to the reconstruction of cloud-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Optimal Interpolation (OI) and data assimilation techniques are traditionally used to provide gap-free datasets. These approaches are often complex and based on a number of assumptions and parameterizations (Miles and He, 2010;Zhao and He, 2012;Fablet et al, 2018). An alternate approach is to use Data Interpolation Empirical Orthogonal functions (DINEOF) FIGURE 14 | The scatter plot between in situ data and reconstructed SST using DINEOF and in situ validation data for user case study 3 during the period 2006-2015.…”
Section: User Case Study 3: Reconstruction Of Daily Cloud Free Modis mentioning
confidence: 99%
“…Optimal Interpolation (OI) and data assimilation techniques are traditionally used to provide gap-free datasets. These approaches are often complex and based on a number of assumptions and parameterizations (Miles and He, 2010;Zhao and He, 2012;Fablet et al, 2018). An alternate approach is to use Data Interpolation Empirical Orthogonal functions (DINEOF) FIGURE 14 | The scatter plot between in situ data and reconstructed SST using DINEOF and in situ validation data for user case study 3 during the period 2006-2015.…”
Section: User Case Study 3: Reconstruction Of Daily Cloud Free Modis mentioning
confidence: 99%
“…The catalog is used for inferring the system dynamics and for building estimates of the system state at unobserved locations and times. Realistic applications to oceanic data include the interpolation of SST (Fablet et al 2018b) and the interpolation of SSH (Lguensat et al 2019). Lguensat et al (2019) have shown in particular how AnDA can be used for improving OIbased SSH fields at fine scale.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, data interpolation and noise reduction are commonly performed using univariate methods as, for example, [1]. Multivariate methods have also been applied to generate uniform products that combine information from different sensors; examples of multivariate approaches include optimal interpolation [2], empirical orthogonal functions [3,4], classification methods [5] and more recently using data-diven methods as analog data assimilation [6,7]. The method discussed in this paper is based on the empirical perception that fronts, eddies, and filaments are identifiable in the satellite imagery of different ocean variables (sea level, ocean color, sea surface temperature, sea surface salinity) and, sometimes, even in the raw radiance recorded by the satellites [8,9].…”
Section: Introductionmentioning
confidence: 99%